Child-Friendly Justice – Czech Perspective - Kissová, Veronika (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:The perception of a child as an object of the rights of others and an object of protection by law has shifted to treating a child as an active subject endowed with their own legal rights since the Convention on the Rights of the Child. This change has been reflected in legal orders of the signatory countries, including the Czech Republic, which recognises the right of children to participate in any proceedings which concern them. This contribution presents various aspects of children’s participation and practical issues of enforcement of the child’s procedural rights from the point of view of the current legislation and the corresponding case-law.Keywords: participation rights, legal proceedings, minor, right to be heard, right to information, representation, children, child-friendly justice